Leveling the Participatory Field: the Mind’s Eye Program at the Guggenheim Museum - Krantz, Georgia (Disability Studies Quarterly, 2013)
This essay constitutes a methodological inquiry into standard approaches to interacting around art with people who are blind or have low vision. Critical reflection upon Verbal Imaging and close-looking techniques yields learning environments in which visitors to the museum have opportunities for increased independence, leadership roles and sense of community. Key words: Guggenheim Museum, art education for blind and low-vision people, verbal imaging, verbal description of art, museum accessibility programs.